Urban agriculture during economic crisis: lessons from Cuba, Sri Lanka and Ukraine - Adam-Bradford, A.; Drechsel, Pay (International Water Management Institute, 2023)
Economic crises take different forms and occur for various reasons, such as political conflicts and pandemics. What all these crises have in common is that they cause disruption to rural-urban food supply chains, resulting in food shortages for the urban poor, with the most direct impact being an increase in food prices. It is within this challenging context that we present empirical examples of the role of urban agriculture.